Cortical remodeling across the lifespan in healthy brain reveals structural network vulnerability to neurodegeneration. (December 2021) - Agosta, Federica; Basaia, Silvia; Cividini, Camilla; Spinelli, Edoardo Gioele; Castelnovo, Veronica; Leocadi, Michela; Calderaro, Davide; Magno, Maria Antonietta; Canu, Elisa; Filippi, Massimo
Abstract: Background: Aging is the main risk factor for most of the neurodegenerative diseases. The aim of this study was to investigate typical cortical thinning changes across lifespan in the healthy brain revealing structural network vulnerability to neurodegeneration. Method: The cohort included 128 healthy individuals aged 20‐85 years that underwent an MRI scan. Structural T1‐weighted images were used to estimate vertex‐wise cortical thickness maps, then grouped into 83 regions. For each region, cortical thickness trajectory with advancing age was estimated, including sex as covariate. Additionally, all regions were ranked based on their relative thickness at the end of the observed lifetime, assessing regional changes over time. Finally, regional mean thickness was correlated with relative change over time. Result: The highest cortical thinning was observed in the temporal lobe (parahippocampal, entorhinal, superior and middle temporal and fusiform), in the frontal lobe (lateral orbitofrontal, superior and inferior frontal and rostral anterior cingulate), in the parietal lobe (the isthmus of cingulate, precuneus, supramarginal and inferior parietal) and in the insular cortex. Interestingly, occipital regions (cuneus, lateral occipital, lingual, pericalcarine), and motor and premotor areas (precentral, postcentral and paracentral regions) showed the least cortical thickness change relative to the whole brain. Finally, positive correlation was found between mean regional thickness and its relative change over time. Conclusion: This study highlights structural vulnerability of brain regions to aging. Furthermore, results provide information concerning trajectories of normal brain aging, identifying those areas that might be more vulnerable to the attack of neurodegeneration. Supported by: European Research Council (StG‐2016_714388_NeuroTRACK).